Pengaruh Rotasi Kerja dan Budaya Organisasi terhadap Prestasi Kerja pada PT Bringin Karya Sejahtera Jakarta Pusat - sholikin, ahmad; Madiistriyatno, Harries; Taufik, Kemal (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study investigates the impact of job rotation and organizational culture on employee performance at PT Bringin Karya Sejahtera, a B2B marketplace company located in Central Jakarta. The background of the study highlights the increasing importance of human resources management and employee adaptability in a competitive and dynamic business environment. The research aims to (1) examine the effect of job rotation on employee performance, (2) analyze the influence of organizational culture on employee performance, and (3) assess the simultaneous impact of both variables on work performance. Using a quantitative approach, the study employed a survey method by distributing questionnaires to 93 employees. The collected data were analyzed using multiple linear regression with SPSS version 26. The results show that both job rotation and organizational culture have significant and positive effects on employee performance. The t-test results indicate that job rotation and organizational culture individually influence performance, while the F-test confirms a joint effect of both variables. The Adjusted R Square value of 0.877 suggests that 87.7% of the variation in employee performance is explained by the two independent variables, with the remaining 12.3% attributed to other factors not examined in this study. These findings suggest that effective job rotation programs and a strong organizational culture can enhance employee productivity and organizational success.